Pengaruh Fraksinasi Terapi Radiasi Terhadap Body Mass Index Pada Kanker Kepala Leher Di Beberapa Instalasi Onkologi Radiasi - Ismil banida nuryaman (Jurnal Imejing Diagnostik (JImeD), 2022)
ABSTRACTBackground: Radiotherapy is the main therapy for the treatment of malignancies, one of which is nasopharyngeal cancer. Radiotherapy uses megavolt (mV) energy to kill cancer cells, therefore radiation is given in fractionation so that healthy cells around tumors can repair themselves. The fractionation was given five times a week with a total of 33 fractions. Besides having a curative effect, radiotherapy can also cause side effects. Radiation is given to the head and neck area, causing the upper digestive organs to experience side effects that reduce the patient's food intake and decrease body weight and body mass index (BMI).Methods: The research design used is descriptive analytic by observing, Analysis using SPSS Version 24.00 Chi-Square test program (p0.05)., and using a questionnaire. This study was conducted in the Radiotherapy Installation of oncology radiation of MRCCC Siloam Semanggi, RSPAD Gatot Soebroto, Dharmais Cancer Hospital, PS.Minggu Hospital, Santosa Bandung Kopo Hospital and Siloam TB Simatupang in July-October 2021 using primary data with a sample of 108 radiotherapy patients for nasopharyngeal cancerResults: In average HNC patients experienced decrement of 3.61 of their BMI and weight loss of 9,77 kg until the last week of radiotherapy. The biggest decrement of BMI occured in the third to fourth weeks of radiotherapy. Patients who undergoing radiotherapy and chemotherapy had a bigger BMI decrement than patients who undergoing radiotherapy only. as radiotherapy side effects to BMI decrement in HNC patients after radiotherapy treatment.Conclusions: Based on the results of this study, it can be concluded that all nasopharyngeal cancer patients who underwent radiotherapy experienced a decrease in BMI and also experienced side effects of xerostomia or dry mouth. Keywords: Fractionation, radiotherapy, Nasopharyngeal Cancer, Body Mass Index, Xerostomia